2022
DOI: 10.1177/0961463x221083788
|View full text |Cite
|
Sign up to set email alerts
|

In their own time: Refugee healthcare professionals’ attempts at temporal re-appropriation

Abstract: Scholarship on refugee labour market participation regularly alludes to the temporal dimension of the process, yet explicit engagement with it remains limited. I argue that researching the temporalities of refugee employment re-entry is valuable as it discerns the recursive interrelation between social structure and individual agency that advances or curbs the labour market trajectories of refugees. Namely, refugees’ perceptions of time inform their integration pathways. In this article, I interrogate how high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Few initiatives specifically target highly skilled asylum seekers, as it is uncertain whether they will be granted the right to stay. These persons can benefit from labour market preparation initiatives while they are waiting for a decision on their asylum claim, enabling them to turn “professional dead‐time” (Mozetič, 2022b: 425) into “productive” time.…”
Section: Results and Discussion: Unpacking “The System”mentioning
confidence: 99%
See 2 more Smart Citations
“…Few initiatives specifically target highly skilled asylum seekers, as it is uncertain whether they will be granted the right to stay. These persons can benefit from labour market preparation initiatives while they are waiting for a decision on their asylum claim, enabling them to turn “professional dead‐time” (Mozetič, 2022b: 425) into “productive” time.…”
Section: Results and Discussion: Unpacking “The System”mentioning
confidence: 99%
“…Employment officers and job coaches can be crucial actors in helping refugees navigate "the system", as Mozetič (2022b) shows in a study of refugee healthcare professionals in Malmö. While informants in Mozetič's study reported that PES employment officers provided the information they needed to pursue their professional goals, some refugees in other studies (Blasko, 2023;Bucken-Knapp, Fakih, & Spehar, 2019;Spehar, 2021) felt that their PES employment officers did not meet their support needs.…”
Section: Abour Marke T Integ R Ation Of Refug Ee S In Sweden: a Multi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Language was perceived to be an obstacle by refugee doctors in every included study. Specific challenges included a lack of medical language courses, 30,34,38,46 unfamiliar abbreviations, 36 and difficulties understanding patients who ‘did not speak clearly due to their illness, their age or their way of speaking’ 37 . Existing courses were often insufficient for medical language 46 .…”
Section: Resultsmentioning
confidence: 99%
“…A strong sense of professional pride motivated doctors to overcome challenges towards full integration. 33,34,41,42,44,46 Those who identified as educators relished the opportunity to teach and be appreciated for their teaching, promoting integration. 41 Some refugee doctors had to change 43 or lower 33 their expectations about their future career paths in order to fully integrate:…”
Section: Professional Identitymentioning
confidence: 99%